A MSALL quantitative method for the determination of Poloxamer 188 in rat plasma by UHPLC–Q‐TOF/MS and its application to pharmacokinetic study. (28th October 2021) - Feng, Yixuan; Li, Lele; Li, Yuxuan; Zhou, Xinxin; Lin, Xiaoying; Cui, Yue; Zhu, Heyun; Feng, Bo
Abstract: Poloxamer (PL)188 is a commonly used pharmaceutical excipient with unique physicochemical properties. In this study, an MS ALL quantitative method for the determination of PL188 in rat plasma by UHPLC–Q‐TOF/MS was developed and validated. PL188 was analyzed on PLRP‐S reversed‐phase column (50 × 4.6 mm, 8 μm, 1, 000 Å) with mobile phase 0.1% formic acid–water and 0.1% formic acid in acetonitrile–isopropanol (2:3, v/v). The liner range was 0.1–10.0 μg/ml. A pharmacokinetic study was performed on rats at a dose of 5 mg/kg by intravenous injection. The pharmacokinetic parameters of intravenous injection were as follows: half‐life was 2.0 ± 1.1 h, volume of distribution was 5.1 ± 3.2 L/kg, area under the concentration–time curve was 3.0 ± 0.6 μg/L h and clearance was 1.7 ± 0.3 L/h/kg. The results indicated that PL188 could be rapidly distributed to tissues with a high clearance rate. This study can provide a good reference for the further study of PL188.